1990
DOI: 10.3109/10715769009109677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glutathione and N-Acetylcysteine on in Vitro and in VIVO Cardiac Toxicity of Doxorubicin

Abstract: The effects of two sulfhydryl compounds, glutathione (GSH) and N-acetylcysteine (NAC), on the cardiotoxicity of doxorubicin (DXR) were tested on in vitro and in vivo models. DXR was administered to rats as 4 weekly i.v. doses of 3 mg/kg. GSH (1.5 mmoles/kg), given i.v. 10 min before and 1 hr after DXR, was found to prevent the development of the delayed cardiotoxic effects of DXR, as assessed by electrocardiographic and mechanical parameters, as well as by histological examination of left ventricular preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Doxorubicin is known to decrease GSH content (106,125,158), a vital antioxidant in striated muscle. Infusion of glutathione prevented the cardiac contractile impairment caused by doxorubicin (256). Other antioxidants also protect cardiac muscle function in doxorubicin-induced cardiotoxicity.…”
Section: Cardiac Musclementioning
confidence: 97%
“…Doxorubicin is known to decrease GSH content (106,125,158), a vital antioxidant in striated muscle. Infusion of glutathione prevented the cardiac contractile impairment caused by doxorubicin (256). Other antioxidants also protect cardiac muscle function in doxorubicin-induced cardiotoxicity.…”
Section: Cardiac Musclementioning
confidence: 97%
“…Based on the free radical hypothesis of cardiac damage, scavengers of free radicals have been evaluated. Classic antioxidants such as vitamin E [71], ascorbic acid [72] and N-acetyl cysteine [73], although having displayed very encouraging preclinical results and in pathophysiologic rationale, have not demonstrated clear benefits in clinical trials. Newer studies involving coenzyme Q [74] and flavonoids [75] have shown beneficial effects although this was not conclusive.…”
Section: Cardioprotective Agentsmentioning
confidence: 99%
“…Epirubicin (4'-epidoxorubicin) and pirarubicin (4'-O-tetrahydropyranyldoxorubicin) have been brought into routine clinical usage after it was observed that they produced less cardiotoxicity than doxorubicin and daunorubicin, the reference molecules, in both preclinical models and early clinical trials (Ganzina, 1983;Maehara et al, 1989;Herait et al, 1992). In addition, several strategies for reducing cardiotoxicity of anthracyclines have been proposed, including the administration of a-tocopherol (Julicher et al, 1986;Mimnaugh et al, 1981), N-acetylcysteine (Villani et al, 1990), glutathione (Villani et al, 1990), and ICRF-187 or dexrazoxane (Herman & Ferrans, 1986;Speyer et al, 1988). This last molecule has been shown to provide a prolonged protection against anthracycline cardiotoxicity in rabbits and dogs (Herman & Ferrans, 1986;Herman et al, 1988) and to prevent the doxorubicin-induced decrease of the left ventricular ejection fraction in human subjects (Speyer et al, 1988;.…”
Section: Introductionmentioning
confidence: 99%